A Maxillary Second Premolar with Four Canals: A Case Report - Karamifar, Kasra; Tondari , Afsoon (Iranian Endodontic Journal, 2021)
Profound knowledge of the internal anatomy and configuration of the teeth plays a pivotal role in the success of standard root canal treatment. The presence of unexpected extra root canals has been reported in all the teeth, making root canal treatment a challenge for every clinician. Although the maxillary second premolar is no exception to this rule, the presence of a variety of multiple canals is relatively rare. In fact, the presence of three separate root canals has been reported in only 1-6% of cases. A 33-year-old male was referred for root canal retreatment of his left maxillary second premolar. An intraoral periapical radiograph revealed previous substandard endodontic treatment. Retreatment was performed under an operating microscope, and four root canals were found, which is, in fact, very rare. This case highlights another variation in the morphology of such teeth and it does highlight the importance of using magnification, especially an operating microscope in endodontic treatment.